The pilot acoustic indicator: a novel cockpit instrument for the greener helicopter pilot - Rolando, A.; Rossi, F.; Riboldi, C.E.D.; Trainelli, L.; Grassetti, R.; Leonello, D.; Redaelli, M. (My University, 2015)
This paper presents the Pilot Acoustic Indicator (PAI), one the outcomes of the Clean Sky GRC5 project MANOEUVRES. The PAI is an instrument designed to present information on the current and expected noise emission levels to the rotorcraft pilot, to allow him/her to adequately react to incipient high noise conditions and effectively fly low acoustic impact procedures, such as in terminal manoeuvres. In-flight noise estimation is based on the interpolation within a pre-calculated database of acoustic hemispheres interrogated through the retrieval of a limited set of current rotorcraft state parameters. Noise information is subsequently synthesized in an index for cockpit display, through a dedicated graphical interface. The paper details the PAI design, development and prototypal implementation, aimed to be integrated in an industrial research flight simulator for functional demonstration and assessment.
Keywords: Green Rotorcraft